IRES-driven translation is stimulated separately by the FMDV 3′-NCR and poly(A) sequences - López de Quinto, Sonia (Oxford University Press, 2002)
The 3′ end region of foot-and-mouth disease virus (FMDV) consists of two distinct elements, a 90 nt untranslated region (3′-NCR) and a poly(A) tract. Removal of either the poly(A) tract or both the 3′-NCR and the poly(A) tract abrogated infectivity in susceptible cells in the context of a full-length cDNA clone. We have addressed the question of whether the impairment of RNA infectivity is related to defects at the translation level using a double approach. First, compared to the full-length viral RNA, removal of the 3′ sequences reduced the efficiency of translation in vitro. Secondly, a stimulatory effect of the 3′ end sequences on IRES-dependent translation was found in vivo using bicistronic constructs. RNAs carrying the FMDV 3′ end sequences linked to the second cistron showed a significant stimulation of IRES-dependent translation, whereas cap-dependent translation was not affected. Remarkably, IRES-dependent stimulation exerted by the poly(A) tract or the 3′-NCR seems to be the result of two separate events, as the 3′-NCR alone enhanced IRES activity on its own. Under conditions of FMDV Lb protease-induced translation shut-off, the stimulation of IRES activity reached values above 6-fold in living cells. A northern blot analysis indicated that IRES stimulation was not the consequence of a change in the stability of the bicistronic RNA produced in transfected cells. Analysis of the RNA-binding proteins interacting with a mixture of 3′ end and IRES probes showed an additive pattern. Altogether, our results strongly suggest that individual signals in the viral 3′ end ensure stimulation of FMDV translation.